International Perspectives on English Language Teacher Education
XII, 202 p.
Keywords: The chapters in this volume outline and discuss examples of teacher educators in diverse global contexts who have provided successful self-initiated innovations for their teacher learners. The collection suggests that a way forward for second language teacher preparation programs is through 'reflective practice as innovation'.